Zooming in on trophy hunter's spending - Saayman, M., speaker; van der Merwe, P., speaker; van Hoven, Wouter, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
The purpose of this paper is to determine the determinants of trophy (international) hunters spending in South Africa. Hunters in South Africa can be divided into two categories namely biltong (primarily local hunters) and trophy (primarily foreign hunters) and hunting makes a significant contribution to the tourism industry and the economy in general. One of the key contributors or ingredients of economic impact studies is tourists (hunters) spending, and the 9000 international hunters spend approximately R1.2 billion in 2013 which can still be increased. The reason being that hunting lodges and game farmers are mostly located in rural provinces with high rates of unemployment. Therefore this research can help practitioners and marketers alike to focus their marketing and development activities and resources on these variables. The research was conducted by means of a structured web based questionnaire survey and this is the first time that the determinants have been identified in South Africa which has a vibrant hunting industry.
Zooming in on trophy hunter spending in South Africa
Zooming in on trophy hunting spending in South Africa
Moderator: Wouter van Hoven.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Presenter: Melville Saayman.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses